2012
DOI: 10.1653/024.095.0232
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Fall Armyworm,Spodoptera frugiperda(Lepidoptera: Noctuidae), at Santa Isabel, Puerto Rico, to Different Insecticides

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…The remaining islands range in area from 13 km 2 to 1800 km 2 , sizes that can only be expected to support a small local population that are prone to abrupt changes in genetic composition or numbers due to genetic drift or migration (reviewed in [ 29 ]). In contrast, the more expansive island of Puerto Rico (9,104 km 2 ) supports large and stable fall armyworm populations [ 24 , 30 , 31 ]. Given these factors, our premise is that fall armyworm populations in Puerto Rico to the north and South America to the south were the principle sources for island-scale immigration in the intervening islands of the Lesser Antilles.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining islands range in area from 13 km 2 to 1800 km 2 , sizes that can only be expected to support a small local population that are prone to abrupt changes in genetic composition or numbers due to genetic drift or migration (reviewed in [ 29 ]). In contrast, the more expansive island of Puerto Rico (9,104 km 2 ) supports large and stable fall armyworm populations [ 24 , 30 , 31 ]. Given these factors, our premise is that fall armyworm populations in Puerto Rico to the north and South America to the south were the principle sources for island-scale immigration in the intervening islands of the Lesser Antilles.…”
Section: Introductionmentioning
confidence: 99%
“…S. frugiperda can develop resistance very rapidly. For example, in Puerto Rico, flubendiamide, chlorantraniliprole, spinosad, and spinetoram were considered as effective pesticides to control S. frugiperda in 2012, but by 2018, S. frugiperda had developed high levels of resistance to a variety of new insecticides in Puerto Rico, such as flubendazole (500 times) and chlorantraniliprole (160 times) ( Belay et al 2012 , GutiĂ©rrez-Moreno et al 2019 ).…”
mentioning
confidence: 99%
“…Some of the synthetic insecticides reported by those authors corroborate the findings of the present study. For example, Belay et al [ 25 ] reported >60% FAW mortality 16 h after application of Radiant, Orthene, and Larvin. In another study, Intrepid 2F, Lannate 2.4LV, Sevin XLR Plus 4F, and Tracer 4SC effectively reduced FAW larvae under field conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%